Endometriosis burden and trends among women of childbearing age from 1990 to 2021 - Tang, Zhongyun; Ma, Chao; Liu, Jin; Liu, Chongdong (Frontiers in Endocrinology, 2026)
BackgroundEndometriosis is a common disease among women of childbearing age (WCBA), significantly affecting their physiological health. This study systematically analyzes the global, regional, and national burden of endometriosis in WCBA based on the Global Burden of Disease 2021 (GBD 2021) database.MethodsThis study focuses specifically on the WCBA population, evaluating the burden of endometriosis in terms of incidence, prevalence, mortality, and disability-adjusted life years (DALYs).ResultsGlobally, the number of prevalent cases of endometriosis among WCBA increased from 19.08 million in 1990 to 21.05 million in 2021, marking a 10% rise; incident cases grew from 3.326 million to 3.439 million, an increase of 3%; DALYs rose from 1.759 million to 1.939 million, a 10% increase; and deaths increased from 21.55 to 46.72, a rise of 117%. However, the age-standardized incidence, prevalence, and DALY rates showed downward trends, with EAPCs of -0.94, -1.12, and -0.93, respectively. Regions with a middle SDI level recorded the highest numbers of prevalent cases, incident cases, DALYs, and deaths. In 2021, endometriosis exhibited marked age-related differences worldwide. Women aged 25–29 had the highest number of prevalent cases and DALYs, those aged 20–24 had the highest incidence, and those aged 45–49 had the highest number of deaths.ConclusionThe global distribution of endometriosis varies significantly across regions, highlighting the need for public health policies to be tailored to regional contexts to optimize healthcare resource allocation.